LEPTIN BEHAVIOR IN DIFFERENT METHODS OF EXERCISE (Fiep Bulletin - online, 2012)
Advances in endocrinologic studies point to the adipocyte as more than a tissue, he comes to synthesize substances such as tumor necrosis factor alpha, interleukin-6 and leptin. In this case, here the leptin deserves the attention for being allocated to food intake, thus characterizing the satiety hormone food. However, this literature review will look at the exercise as a way of modulating production of leptin in the body, discussing different methodologies of exercise tested by researchers in different populations.
Keywords: leptin; satiety; exercise